2022
DOI: 10.3390/cells11040685
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Rehabilitation and Stem Cell Therapy Targeting Chronic Spinal Cord Injury: A Review of Preclinical Studies

Abstract: Stem cell medicine has led to functional recovery in the acute-to-subacute phase of spinal cord injury (SCI), but not yet in the chronic phase, during which various molecular mechanisms drastically remodel the tissue and render it treatment-resistant. Researchers are attempting to identify effective combinatorial treatments that can overcome the refractory state of the chronically injured spinal cord. Regenerative rehabilitation, combinatorial treatment with regenerative medicine that aims to elicit synergisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 72 publications
0
17
0
2
Order By: Relevance
“…The outcomes of combination therapy in regenerative treatments have recently been reported by Tashiro et al, both in the injured spinal cord where cells were transplanted and also distant from the lesion 17 . Improved survival was one benefit of rehabilitation training on transplanted cells 28 , 29 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The outcomes of combination therapy in regenerative treatments have recently been reported by Tashiro et al, both in the injured spinal cord where cells were transplanted and also distant from the lesion 17 . Improved survival was one benefit of rehabilitation training on transplanted cells 28 , 29 .…”
Section: Discussionmentioning
confidence: 84%
“…Although Tashiro et al showed that combined treatment was significantly more effective for functional recovery than non-treatment, they could not demonstrate the superiority of the combination therapy over the single therapies. The mechanism by which combined treatment improves motor function after SCI, regardless of the phase, is yet to be fully elucidated 17 . Furthermore, there is currently no research that investigates the combined effect of rehabilitative training with any iPS cell-derived cell lines, which have attracted wide attention for their application in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…This study suggests that spasticity should not be overlooked as a potential adverse effect of serotonergic pharmacotherapy. The reason why Ryu et al did not detect significant locomotor recovery may be related to the phase of SCI; chronic SCI is refractory to various treatments, and the characteristics of the late-subacute phase are similar to those of chronic SCI [ 20 ]. Ung et al further applied buspirone, carbidopa, and L-DOPA in combination with TMT to activate the central pattern generator.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of molecules is reportedly modified secondary to training, with upregulation of various neurotrophic factors, including brain-derived neurotrophic factor (BDNF), neurotrophin 3 (NT3), neurotrophin 4 (NT4), glial-cell-line-derived neurotrophic factor (GDNF) [ 17 ], nerve growth factor (NGF) [ 18 ], and insulin-like growth factor-1 (IGF-1) in acute-to-subacute SCI [ 19 ]. Neurotrophic factors promote neural plasticity, vascularization, and neuroprotection and are considered to underlie the abovementioned beneficial changes [ 20 ]. Furthermore, it was reported that physical-activity-mediated functional recovery involves endogenous neural stem cells (NSCs) [ 21 ] and that TMT promotes the proliferation and migration of ependymal cells, an endogenous source of NSCs [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI) is a common disorder. The prevalence of traumatic SCI worldwide is estimated to be 236–1298 individuals per million with an annual incidence ranging from 8 to 246 individuals per million [ 1 ]. SCI is a devastating injury that results in partial or complete loss of motor, sensory, and autonomic functions [ 2 ].…”
Section: Introductionmentioning
confidence: 99%